Sistematični pregled raziskav vrednotenja koristi klinične farmacije in farmacevtske skrbi - Kos, Mitja (Farmacevtski vestnik, 2012)
Aim of the manuscript is a systematic review of studies that evaluated benefits of clinical pharmacy and pharmaceutical care. In Medline 266 studies were captured published before 25.11.2011, 253 clinical studies and 13 meta analises. The number of studies corresponds to the uptake of pharmaceutical care concept in nineties and amounts 20 studies published on a yearly basis after 2009. The highest number of studies evaluated services in USA, Canada and Australia. In Europe the first studies were published in UK and Sweden in the last years of the 20th century. The highest number of studies evaluated services performed in general physicians' clinics and in community pharmacies. Most often studies evaluated pharmaceutical services for the patients with hypertension, asthma, diabetes, heart failure, bacterial infection and depression. Of particular importance are studies evaluating polypharmacy. Results of the majority of studies, but not all, show positive outcomes of clinical pharmacy and pharmaceutical care.
Keywords: farmacevtska skrb; klinična farmacija; pregled; raziskave